Halal Knowledge, Religiosity, and Halal Awareness: Determinants of Generation Z Consumers Purchase Decision - Sefni Novita Sari; Dessi Susanti (Journal of Consumer Sciences, 2025)
Background: Recently, the demand for halal cosmetic goods has significantly expanded, particularly among Generation Z customers in West Sumatera, Indonesia. Notwithstanding their robust religious base, the understanding of halal cosmetics is still fairly confined.